ASSOCIATION OF SERUM URIC ACID LEVEL WITH SHORT TERM IN-HOSPITAL MORTALITY IN ST ELEVATION MYOCARDIAL INFARCTION - Hassan, Faheem Ul; Ahmed, Ijaz; Shah, Naveed Ahmed; Tariq, Farhan; Shah, Jamil Ahmed; Afaq, Saima (Pakistan Armed Forces Medical Journal, 2020)
Objective: Association of raised serum uric acid level with short term in-hospital mortality in ST elevation myocardial infarction. Study Design: Cohort study. Place and Duration of Study: Army Cardiac Centre Lahore, from Oct 2014 to Sep 2015. Methodology: Total of 420 patients, males and females with ST elevation myocardial infarction were recruited from Emergency Department, Army Cardiac Centre Lahore. Samples for serum uric acid were sent at reception. Patients were divided into two groups according to serum uric acid level. Both groups received same treatment. Assessment was done by medical history, physical examination, baseline investigations including ECG and cardiac enzymes at reception and monitoring continued till 07 days. Results: Out of 420 cases (210 in each group), mean age ± SD was calculated as 50.66 ± 8.19 and 48.14 ± 7.69 years respectively. Males were 57.14% and 61.43% in group A and group B respectively while females were 42.86% and 38.57% respectively. Mean serum uric acid levels were calculated as 8.52 ± 0.30 mg/dl in group A and 5.55 ± 0.31 mg/dl in group B. Frequency of in hospital mortality was recorded as 12.86% in group A and 3.33% in group B while 87.14% in group A and 96.67% in group B were discharged. A p-value was calculated as 0.000 showing a significant difference, Relative risk was calculated as 3.8571. Conclusion: Raised serum uric acid level is significantly associated with short term in-hospital mortality in ST elevation myocardial infarction.